Efficiency of the Training Program for Developing Volleyball Players' Coordination Abilities at the Stage of Specialized Basic Training (Physical Culture and Sport: Scientific Perspective, 2024)
The search direction for effective training means is connected with the analysis of volleyball players' competitive activities, which involves solving coordinationally complex motor tasks in constantly changing conditions with a severe time deficit. A wide range of factors affecting the success of game activities underscores the importance of improving the mechanisms of adaptation and restructuring of the athlete's motor skills according to the demands of the game situation. To establish the effectiveness of a training program for developing volleyball players' coordination abilities at the stage of specialized basic training. Theoretical analysis and synthesis of scientific and methodological literature data, pedagogical observation, pedagogical experiment, and methods of mathematical statistics. The research was conducted at the Ivan Boberskyj Lviv State University of Physical Culture and VC "Lvivyanka-LSUPC-SKIF." Control of physical and coordination training indicators of volleyball players and analysis of competitive activities were performed according to developed protocols. During the study, a significant increase in the ability to maintain static balance (p
Keywords: coordination abilities; training; volleyball players; efficiency; performance indicators; pedagogical experiment